Summer Activity Patterns of Three Rodents in the Southwestern Yukon - Gilbert, B.S.; Cichowski, D.B.; Talarico, D.; Krebs, C.J. (ARCTIC, 1986)
The small mammal communities of boreal forest in the SW Yukon are diverse and little is known about the underlying reasons for this species richness. Niche differentiation through staggered periods of activity is one way in which similar species may avoid potential interference competition. In this study we describe the activity pattern of three rodents (the deer mouse, the northern red-backed vole, and the singing vole) from the summer solstice to the autumnal equinox. Activity was measured on two white spruce plots by checking live-traps at 2 h intervals over a 24 h period. We did this at monthly intervals between June and September 1984. The deer mouse was strongly nocturnal throughout the summer, while the northern red-backed vole and the singing vole were active both day and night. During the nocturnal period of deer mouse activity, approximately 80% of the red-backed vole population was active, and we conclude that there is no evidence of temporal niche differentiation between these two species. Only deer mice showed a seasonal change in activity pattern. As the days became shorter, deer mice became active earlier, so that by September they were active 4 h earlier than they were in June.Key words: deer mice, Peromyscus maniculatus, northern red-backed vole, Clethrionomys rutilus, singing vole, Microtus miurus, activity time, Yukon, competition Mots clés: souris sylvestre, Peromyscus maniculatus, campagnol à dos roux boréal, Clethrionomys rutilus, campagnol chanteur, Microtus miurus, période d'activité, Yukon, compétition